2022
DOI: 10.3390/cells11223658
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine Enhances the Integrity of the Blood–Milk Barrier and Inhibits Oxidative Stress in Lipopolysaccharide-Stimulated Mastitis

Abstract: Mastitis is a common clinical disease which threatens the welfare and health of dairy cows and causes huge economic losses. Sanguinarine (SG) is a plant-derived alkaloid which has many biological functions, including antibacterial and antioxidant properties. The present study attempted to evaluate the effect of SG on lipopolysaccharide (LPS)-induced oxidative stress reactions and explore its potential mechanisms. The expression profile of SG was analyzed by network pharmacology, and it was found that different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Similarly, dietary supplementation of 200 mg/kg MCE observably alleviated oxidative stress induced by enterotoxigenic Escherichia coli in mice, as illustrated by lower levels of MDA and increased activities of CAT and GSH-Px ( 18 ). It has been reported that sanguinarine not only decreased the ROS level induced by LPS, but also increased the activity of antioxidant enzymes by activating the Nrf2 signaling pathway in mouse mammary epithelial cells ( 34 ). Moreover, sanguinarine can inhibit the activities of nicotinamide adenine dinucleotide phosphate oxidase 2, thereby inhibiting the conversion of NADPH to ROS and improving the antioxidant capacity ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dietary supplementation of 200 mg/kg MCE observably alleviated oxidative stress induced by enterotoxigenic Escherichia coli in mice, as illustrated by lower levels of MDA and increased activities of CAT and GSH-Px ( 18 ). It has been reported that sanguinarine not only decreased the ROS level induced by LPS, but also increased the activity of antioxidant enzymes by activating the Nrf2 signaling pathway in mouse mammary epithelial cells ( 34 ). Moreover, sanguinarine can inhibit the activities of nicotinamide adenine dinucleotide phosphate oxidase 2, thereby inhibiting the conversion of NADPH to ROS and improving the antioxidant capacity ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mastitis not only causes a quantity of economic losses in the global dairy industry every year, but also brings enormous pain to lactating women [2,3]. The causes of mastitis are diverse, among which bacterial invasion is considered one of the main reasons, and Gram-negative bacteria is considered to the main pathogen [4].…”
Section: Introductionmentioning
confidence: 99%